Barbados : financial system stability assessment - update : including reports on the observance of standards and codes on the following topics : banking supervision and securities regulation (IMF WashingtonUS, 2009)
Finds that the Barbadian financial system has proved to be resilient and, so far, has not been affected by the turmoil in mature financial markets. Notes three reform challenges for the authorities.
Keywords: BANKING SYSTEMS